All at once, just once - Peats, Ryann, author; Beachy-Quick, Dan, advisor; Dungy, Camille, committee member; Souza, Caridad, committee member (Colorado State University. Libraries, 2018)
All at Once, Just Once is a collection of poems structured to reflect the cyclical nature of the calendar year as someone who identifies as queer. The first and last sections introduce & explore themes of grief, coming out, defining the self in familial, interpersonal & domestic spaces, and tracing violence in the world. The three center sections include poems of a quieter and concise register that work through explorations of the feminine, nurturance, definitions of "woman," the multiplicity of queer bodies, being in a love relationship, and exploring violence against queer bodies in moments of crisis and healing.